A luminescent double helical gold(i)–thiophenolate coordination polymer obtained by hydrothermal synthesis or by thermal solid-state amorphous-to-crystalline isomerization1. Issue 16 (28th April 2015) - Lavenn, Christophe; Okhrimenko, Larysa; Guillou, Nathalie; Monge, Miguel; Ledoux, Gilles; Dujardin, Christophe; Chiriac, Rodica; Fateeva, Alexandra; Demessence, Aude
<x xml:space="preserve">Abstract</x> The first structure of a luminescent gold thiolate coordination polymer, [Au(SPh)]n.